ANALISIS KETERSEDIAAN BERAS DI JAWA TIMUR - Wijoyo, Bayu Hertanto; Hidayat, Syarif Imam; Abidin, Zainal (Berkala Ilmiah AGRIDEVINA, 2019)
The problem that occurs is their surplus rice production in East Java, but the government still import rice. This research aims : to analyze the influential factor the rice harvested area, rice production, the volume of rice imports, consumptions, the population, the domestic prices of rice and sugar affecting the availability of rice in East Java. The methods used in this research is the multiple linear regression models. The results of the research showed the overall factor has an influence simultaneously ehile the partial factors of rice harvest area, production of rice, the volume of imported rice and the domestic price of rice has a significant positive influence. The significant negative influence derives from rice consumption rate and the domestic price of sugar, meanwhile the population has no influence at all towards the rice availability in East Java particularly in 2007-2017.DOI : https://doi.org/10.33005/adv.v8i2.1799